Justice at Cross Roads a A Critical Analysis of the Functioning of the Indian Judicial System and the Need for an Alternative (Global Journal of Human-Social Science, 2015)
Abstract not found
Keywords: access to justice alternative dispute resolution; adjudication; arbitration; disputant; docketexplosion; indian judicial system; litigation; mediation